FRI0246 Serious infusion-related reactions after rituximab in patients with rheumatoid arthritis: data from the autoimmunity and rituximab registry. (23rd January 2014) - Salmon, J. H.; Ravaud, P.; Bardin, T.; Cacoub, P.; Cantagruel, A.; Combe, B.; Dougados, M.; Flipo, R.-M.; Godeau, B.; Guillevin, L.; Le Loët, X.; Hachulla, E.; et al.
Abstract : Objectives: To evaluate the prevalence of serious infusion-related reactions after rituximab (RTX) in a large prospective registry of patients with rheumatoid arthritis. Methods: The Autoimmunity and Rituximab registry (AIR) is an independent registry promoted by the French Society of Rheumatology that included 1983 patients with rheumatoid arthritis treated with rituximab and followed-up prospectively for seven years. An infusion-related reaction (IRR) was defined as occurring during or in the 24 hours following an infusion. Results: Overall, 45 IRR resulted in RTX discontinuation [2.2% of all patients with RA, 0.4% of all infusions]. These serious IRR occurred after the first cycle in 17 patients, the second cycle in 18, the third cycle in 7, the fourth cycle in 2 patients and after the fifth cycle in 1 patient. Serious IRR mainly occurred after the first infusion of the cycle (71% of the 45 IRR vs 39% after the second infusion). 32 patients (73%) had allergic or anaphylactic manifestations such as a skin rash (18 patients), a throat irritation (8 patients), an anaphylaxis (3 patients), a bronchospasm (2 patients) or an angioedema (1 patient), 5 (11%) hypertension, 3 patients (7%) fever, 4 patients (8.5%) other symptoms and 1 missing data. Among the 30 patients who had a serious IRR after the second or subsequent infusions, 15 (50%) had previously had a milder IRR requiring a transient interruption or a reduction in the infusion flow. There was no fatal infusion-related reaction, and all infusion-related reactions resolved after discontinuation of RTX and symptomatic treatment. Conclusions: The real life frequency of IRR resulting in RTX discontinuation is similar to that observed in clinical studies, approximately 0.5 %. Allergic manifestations were the most frequent. These reactions mainly occurred during the first two cycles, but nearly a quarter of them occurred after the 3d or subsequent cycles. Last, severe reactions had been preceded by a milder infusion reaction to a former infusion in 50% of patients Disclosure of Interest : None Declared